Front Cover: Engineering Molecular Topology: A Pseudopeptidic Macrocyclic Figure‐Eight Motif (Eur. J. Org. Chem. 7/2017). Issue 7 (10th February 2017) - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P; Butcher, Ray; Haridas, V.
Abstract : The cover picture shows the structure of a pseudopeptidic macrocycle. The 32‐membered macrocycle containing four leucine residues, two phenyl rings, and two bispidine units adopts a figure‐eight topology. The turn units in the structure required to form the figure‐eight topology are provided by bispidine and 1, 3‐benzenedicarbonyl linkers. A strategy for the design and synthesis of macrocycles with intriguing topology was developed, which was demonstrated by the synthesis of two macrocycles, one with an open cavity and one with a figure‐eight topology. Details are discussed in the Communication by V. Haridas et al. on page 1120 ff (DOI:10.1002/ejoc.201601365 ).